Imagem de si e escolha de mídias de apocalipse zumbi em universitários: uma leitura analítica - Dias, Gregório do R. M. C. (2016)
This study aimed at evaluating the self-image, the self-esteem and the social skills of university students who consume zombie apocalypse media assiduously. For this, we applied the Self-Image and Self-Esteem Questionnaire and the Questionnaire and Evaluation of Social Skills, Behaviors and Contexts for University Students - QHC -University in 20 university students who consider themselves zombie apocalypse media fanatics. Also, to compare the variables of both questionnaires and seek correlations between one questionnaire and the other, we used the Pearson coefficient and the hypothesis of the t-Student test. Participants showed a relatively good image of themselves and a lower self-esteem compared to this self-image. The results obtained by the QHC -University indicate that most of the participants of this study presents difficulties in modulate how to express themselves, fearing the negative feelings that may arise in their contact with others, preferring a non-confrontational attitude. In this sense, there was evidence of incongruity between how participants see themselves and the way they behave towards other people. A discussion of the possible motivations behind the choice of zombie apocalypse media was made by analyzing these results under the prism of the Analytical Psychology theory. From this, it can be deduced that the participants show a persona somewhat submissive, that avoids conflicts, accompanied by an aggressive and destructive shadow opposing this persona; dark contents to some extent depicted in the zombie apocalypse narratives. Lastly, it appears that these young people deal with their adapting difficulties and negative feelings through a form of escape and the zombie media symbolize the fear of the other, fear of failure, fear of failure and insecurity about themselves